Artificial Intelligence in Healthcare: Insights into MedicalDoctors' Knowledge, Perceptions, and Attitudes in Sokoto, Nigeria (Western Journal of Medical and Biomedical Sciences, 2025)
Artificial intelligence is rapidly transforming many industries, and healthcare is one of the most promising areas. Its integration could fundamentally change how diseases are diagnosed, treated, and managed, as well as improve the overall operation and delivery of healthcare services worldwide. This study aimed to determine the knowledge, perception and attitude of medical doctors towards the use of Artificial intelligence. Using stratified sampling technique, we recruited medical doctors across all cadre of doctors in the clinical departments of Usmanu Danfodiyo University Teaching Hospital and Specialist Hospital in Sokoto, north-western Nigeria. Having obtained informed consent, the data was collected using self-administered questionnaires. It was then analyzed using SPSS V25 for windows and level of significance was set at p
Keywords: Artificial intelligence; Attitude; Knowledge; Medical doctors; Perception